2020
DOI: 10.1002/erv.2806
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volumes in anorexia nervosa at different stages of the disorder

Abstract: Introduction Hippocampus is involved in a range of cognitive and behavioural processes, and its volume has been found to be reduced in different psychiatric disorders. The present study aims at exploring hippocampal volumes in anorexia nervosa (AN) at different stages of the disorder (a few months after onset, more than 1 year after onset and after recovery). Methods Two samples were included in the present study. The first was composed of 58 patients (38 with present AN, 20 full recovered from AN) and 38 age‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
3
9
0
Order By: Relevance
“…The mean volume of the hippocampal complex in patients with acute AN (lh = À3.68%; rh = À4.08%) was significantly lower than in HCs, confirming previous reports of hippocampal volumetric reduction. 17,18,20 Reported rates of cortical thinning in the acute stage of AN (6.4% on average) 1,3 exceed the whole hippocampus volume reduction observed in this study, whereas the volumetric reduction of the amygdala is comparable in magnitude (lh = À4.34%; rh = À4.22%). 28 However, while the direction of the effects in all of the larger subfields aligned with those observed for the entire hippocampus, the spatial distribution of the volumetric reduction within the hippocampus appears more heterogeneous than the pattern of cortical thickness reduction.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The mean volume of the hippocampal complex in patients with acute AN (lh = À3.68%; rh = À4.08%) was significantly lower than in HCs, confirming previous reports of hippocampal volumetric reduction. 17,18,20 Reported rates of cortical thinning in the acute stage of AN (6.4% on average) 1,3 exceed the whole hippocampus volume reduction observed in this study, whereas the volumetric reduction of the amygdala is comparable in magnitude (lh = À4.34%; rh = À4.22%). 28 However, while the direction of the effects in all of the larger subfields aligned with those observed for the entire hippocampus, the spatial distribution of the volumetric reduction within the hippocampus appears more heterogeneous than the pattern of cortical thickness reduction.…”
Section: Discussionsupporting
confidence: 43%
“…Compared with control participants, studies have found volumetric reductions in only one of seven subfields, 16 in 11 of 12 hippocampal subfields, 18 and in six of 18 subfields. 17 Furthermore, it remains unclear whether the observed reductions in subfield volumes are lateralized or can be attributed to particular subfield components, as in these previous studies the subfield volumes were mostly averaged across hemispheres and were defined based on a coarser atlas. Data on Alzheimer disease indicates an increased accuracy of hippocampal estimates when using the newer atlas.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The sample included was similar to a previous study (Collantoni et al, 2020a). A total of 74 patients with AN (54 with acute AN and 20 fully recovered (recAN)), and 54 HW were recruited from two sites.…”
Section: Sample Characteristics and Clinical Assessmentmentioning
confidence: 99%
“…Alterations have been observed in whole‐brain cortical thickness, surface area, grey and white matter volumes, gyrification, and cortical complexity (Collantoni et al., 2020; Seitz et al., 2016; Walton et al., 2022). Along with whole‐brain analyses, researchers also focussed on specific subcortical structures which could play a particular role in the pathogenesis of AN, such as the hippocampus (Beadle et al., 2015; Collantoni et al., 2021), the amygdala (Giordano et al., 2001), and the striatum (Favaro et al., 2014).…”
Section: Introduction and Aimsmentioning
confidence: 99%